Computer graphics through openGL : from theory to experiments - Guha, Sumanta (CRC Press, 2015)
Hello WorldAn Invitation to Computer GraphicsOn to OpenGL and 3D Computer Graphics Tricks of the Trade An OpenGL Toolbox Movers and Shapers Transformation, Animation and ViewingInside Animation: The Theory of TransformationsAdvanced Animation Techniques Geometry for the Home Office Convexity and InterpolationTriangulationOrientation Making Things Up Modeling in 3D Space Lights, Camera, Equation Color and LightTextureSpecial Visual Techniques Pixels, Pixels, Everywhere Raster Algorithms Anatomy of Curves and Surfaces BézierB-SplineHermite Well ProjectedApplications of Projective Spaces The Time.